Anayasacılığımızda “yargı bağımsızlığı” ilkesine ilk vurgu: Fermân-ı adâlet (1875) - SEZER, ABDULLAH (My University, 2023)
Fermân-ı Adâlet (1875), anayasacılık tarihimizde yargı bağımsızlığına ilk kez açık vurgu yapılan belgedir. Söz konusu Ferman’dan bir yıl sonra, 1876’da ilk anayasamız olan Kanun-ı Esasi ilân edilmiştir. Bu çalışmada Ferman’ın anayasa hukuku açısından incelenmesi amaçlanmıştır. Bu çerçevede öncelikle Ferman’ın tarihsel arka planına değinilmiştir. Ardından Ferman’ın kapsam ve içeriği ile katkısı üzerinde durulmuştur. Ferman’da yer alan ilkeler, vurgular ve ifadeler mercek altına alınırken özellikle yargı bağımsızlığı ve hak ve özgürlüklere ilişkin boyutlarına odaklanılmıştır. Bu açıdan bakıldığında ilk anayasanın ilanından bir yıl önce, Ferman’da bu denli önemli konuların vurgulanması dikkate değerdir. Buna karşın, söz konusu Ferman’ın anayasa hukuku literatürümüzde yeterince incelenmemiş ve hatta ihmâl edilmiş olması da eleştirilmelidir. Bu çalışmanın yazarları, Fermân-ı Adalet’in incelenmesine özgülenen makalenin devamı niteliğinde olmak üzere adı geçen belgenin düzeltilmiş bir transkripsiyonunu ve günümüz Türkçesine aktarılmış metnini de yayıma hazırlamaktadırlar

The Imperial Edict On Justice (1875) is a document that is mostly neglected in our constitutional literature. However, the emphasis on the independence of the judiciary in this document is very important. In fact, one year after the Edict, the Kanun-ı Esasi, our first constitution, was promulgated in 1876. This study aims to analyse the Edict in terms of constitutional law. However, before this, the historical background of the Edict has been analysed comprehensively. After analysing the historical development of the Edict, the scope and content of the Edict and its contribution have been emphasised. The principles, emphases and expressions in the Edict are scrutinised. This examination has been made under the dimension of the Edict related to the independence of the judiciary and the dimension related to rights and freedoms. It is noteworthy that the Edict emphasised the independence of the judiciary and rights one year prior to the Kanun-ı Esasi. The fact that it has not been sufficiently analysed an even has been neglected in the constitutional law literature should be criticised. To complement this study, the authors are also preparing a transcription of the Edict of Justice with corrected inaccuracies and a text translated into modern Turkish.
The first emphasis on the principle of “judicial independence” in our constitutionalism: the imperial edict on justice (1875)
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); Fermân-ı Adâlet; Hersek İsyanı; Andrássy Notası; Adalet Dairesi; The Imperial Edict on Justice; The Revolt of Herzegovina; Andrássy Note; The Circle of Justice